Proceedings of the Conference on Dutch Directions in HCI 2004
DOI: 10.1145/1005220.1005229
|View full text |Cite
|
Sign up to set email alerts
|

Using home networks to create atmospheres in the home

Abstract: The Atmosphere Controller is an implementation of home networking technology that could make life at home a totally new experience. An atmosphere is created by combining light (intensity and colour), music and wallpaper projection. To find out if is this type of experience fits into everyday life of people, we studied the current experience of creating atmospheres by conducting interviews and probes studies in people's homes [5]. The same people were later invited to test the application in a Lab environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This approach supports reflection by participants themselves as part of data acquisition (e.g. [48,74]). With this approach, participants take responsibility for and control what information they record or share in the probes [36].…”
Section: Cultural Probes Approachmentioning
confidence: 77%
“…This approach supports reflection by participants themselves as part of data acquisition (e.g. [48,74]). With this approach, participants take responsibility for and control what information they record or share in the probes [36].…”
Section: Cultural Probes Approachmentioning
confidence: 77%
“…Although a generic model can serve as a starting point, atmosphere models need to be personalized to manage the different experience of atmospheres found between subjects. Second, laboratory studies with a basic prototype home atmosphere controller have shown that attachment to the system can be increased by allowing people to add personal content [11]. Possible approaches to personalization include content adaptation and remodeling.…”
Section: Personalization Of the Atmosphere Modelmentioning
confidence: 99%
“…The prototype evoked reactions of astonishment and surprise, and the default atmospheres inspired the participants to create their own, personal atmospheres [11]. Before a semantic model-based atmosphere controller can be deployed in the home, field studies need to examine the degree to which the atmosphere controller will be accepted as part of everyday life.…”
Section: Reflections On Design and Approachmentioning
confidence: 99%